Relationship between indicators of carotid artery rigidity and cognitive functions in arterial hypertension patients - Dotsenko, N. Ya.; Boev, S. S.; Shekhunova, I. A.; Molodan, A. V.; Gerasimenko, L. V.; Malynovskaya , A. Ya. (Modern medical technology, 2019)
Purpose of the study. assessment of relationship between the thickness of the intima-media complex, indicators of carotid artery rigidity state and cognitive dysfunction as a marker of brain damage and the study of their prognostic significance in the development of cognitive impairment in arterial hypertension patients. Material and methods. The subject of the examination was a group of 69 patients with stage II arterial hypertension, grade 2–3, not receiving any antihypertensive therapy or being treated irregularly, aged 51,38 ± 0,94 years. The control group consisted of 12 practically healthy, normotensive individuals aged 54,25 ± 2,74 years, without cognitive impairment. The Montreal Scale (MoCA test) was used to assess cognitive functions. The state of the carotid artery was studied with the help of sonography with recording the thickness of the intima-media complex; Peterson and Young modules, linear tensile properties, radial tension of the vessel wall, parameter β, local pulse wave velocity were calculated. Results. There was a significant increase in the thickness of the intima-media complex in patients without cognitive impairment (0,83 ± 0,02; p < 0,05) and with cognitive impairment (0,89 ± 0,03; p < 0,05) relative to healthy individuals (0,68 ± 0,03) in the absence of significant differences between groups of patients (p > 0,05). Of the remaining indicators of vascular rigidity, only β parameter differed from the control group in patients without cognitive impairment, while in patients with cognitive impairment all studied parameters differed from the control group (p < 0,05). A correlation was established between cognitive impairment and the thickness of the carotid intima-media complex (only with increased values of the carotid intima-media complex thickness – r = 0,62; p < 0,05), with the stiffness index (r = –0,392; p < 0,05), local SPV SA (r = –0,326, p < 0,05). Analysis of the area under the ROC curve 0,60 ± 0,07 (95% CI: 0,47–0,74; p = 0,124) for the indicator of the intima-media complex to determine the likelihood of the development of cognitive impairment in patients with hypertension indicates the unsatisfactory quality of the model. Conclusions. Value of carotid intima-media complex thickness and other indicators of vascular rigidity to determine the likelihood of developing cognitive impairment in patients with poor-quality hypertension (AUC below 0,60) cannot serve as a marker for predicting cognitive dysfunction in patients with hypertensive disease.